2017
DOI: 10.1111/jpc.13618
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the Whitt Neonatal Trigger Score in an ‘at‐risk’ neonatal population

Abstract: The W-NTS observation chart, previously shown to outperform existing early warning scores, acts well as an adjunct to clinical assessment on the PNW, with its simplicity allowing for the successful and safe use by non-paediatric specialists. We recommend that neonates scoring 1 should be reviewed, with a septic screen and commencement of antibiotic therapy considered, while those scoring 2 or more should be strongly considered for NICU admission for further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The W-NTS was produced as an established track and trigger scoring system in neonatal population where early warning systems were unexplored topics. 8 The present prospective evaluation supported the postulated score cutoffs from retrospective research by Holme et al and Robinson et al that a neonate scoring ≥1 was more likely to require a medical review and a score of ≥2 was more likely to require NICU admission. 4,8 It is worth noting here that the outcome of retrospective and prospective chart review indicated that standard of care system was effective in identifying a deteriorating newborn, however, by including NEWS, it helped us to identify them in a timely manner and intervene early.…”
Section: Reliability Of Nts Scoresupporting
confidence: 86%
See 3 more Smart Citations
“…The W-NTS was produced as an established track and trigger scoring system in neonatal population where early warning systems were unexplored topics. 8 The present prospective evaluation supported the postulated score cutoffs from retrospective research by Holme et al and Robinson et al that a neonate scoring ≥1 was more likely to require a medical review and a score of ≥2 was more likely to require NICU admission. 4,8 It is worth noting here that the outcome of retrospective and prospective chart review indicated that standard of care system was effective in identifying a deteriorating newborn, however, by including NEWS, it helped us to identify them in a timely manner and intervene early.…”
Section: Reliability Of Nts Scoresupporting
confidence: 86%
“…The W-NTS is one such scoring system that has been successfully used in UK as an adjunct to clinical assessment by non-specialists, in early identification of neonates requiring extra care. 8 As explained earlier, literature review regarding the use of such scoring system in neonatal population is sparse, hence this prospective observational study was carried out. [3][4][5][6]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations